Standardization of sterilization time and plant bioregulators for callus formation in hybrid Lilium cv. Fangio - ANCHAL ARPITA GOCHHAYAT; SASHIKALA BEURA; ENKETESWARA SUBUDHI (International Journal of Pharma and Bio Sciences, 2017)
An efficient protocol was developed for the bulb scale explants derived callus culture for hybrid Lilium Cv. Fangio under in vitro conditions on Murashige and Skoog basal medium in the Biotechnology-cum-Tissue Culture Centre, Orissa University of Agriculture and Technology, Bhubaneswar. The bulb scale explants were treated with 0.1 % HgCl2 (3 min, 4min, 5min, 6 min, 7min, 8min and 9 min) and control (without treatment) and cultured on MS media, among the treatments, 5 minutes timing resulted in minimum contamination [fungal % (6.67), bacterial % (6.67)] maximum survival % (83.33%). The best surface sterilization time was further taken into consideration for treatment of explants treated for sterilization and cultured in the Basal media supplemented with BAP (0.5, 1.0 mg/l) in combination with 2,4-D (0.5,1.0,1.5,2.0, and 2.5 mg/l) and 2,4-D (0.5,1.0,1.5,2.0, and 2.5 mg/l) alone with control. Basal media supplemented with BAP (1.0 mg/l) and 2,4-D (2.0 mg/l) produced maximum callus % and spread, profuse green callus was also recorded in similar combination which opened prospects for developing an indirect means of in vitro regeneration of hybrid Lilium Cv. Fangio there by strengthening the way biotechnology which could be used for improvement and satiate the national and international demands of this cut flowers.